Towards real-time self-powered sensing with ample redundant charges by a piezostack-based frequency-converted generator from human motions. (15th April 2022) - Li, Zhongjie; Peng, Xuzhang; Hu, Guobiao; Zhang, Dong; Xu, Zhibing; Peng, Yan; Xie, Shaorong
Graphical abstract: Highlights: A piezostack-based frequency-converted generator is proposed. The generator emphasizes ultra-low(<5 Hz) frequency vibration energy harvesting. The peak power is 5.56 W at a running speed of 10 km/h with 39.6 Ω. The redundant charges from 150 s charge time keep a watch running for 50 mins. Abstract: This paper presents a piezostack-based frequency up-converting generator for scavenging ultra-low frequency (lower than 5 Hz) vibration energy associated with human motion. The generator, consisting of a force amplifier, a piezoelectric stack, a spring-mass system, and a spring limiter, realizes ultra-low frequency conversion mainly through the impact-induced frequency conversion effect. To estimate the output voltage of the generator numerically, we built a two-degree-of-freedom (2DOF) equivalent model based on the mechanical structure of the harvester. Moreover, we conducted five series of experiments to investigate the output performance of a fabricated prototype. The prototype generates an instantaneous peak-peak output power of 5.56 W (averaged power of 0.93 mW) excited by human running motions. A 'SHU' LED array was lighted up in real-time successfully. We then tested the performance of the prototype in a real-time self-powered system. The generator is able to power a watch and a thermometer in real-time. More importantly, when the excitation stops, they are powered by redundant charges for approximately 50 minutes and 1 minute, respectively. This research can make an essential contribution to ultra-low frequency vibration energy harvesting and the realization of real-time self-powered wearable devices.